Characterising socio-environmental mining impacts using GIS and remote sensing : a case study in Didipio, Philippines - Ang, Michelle Li Ern (2023)
Mining results in significant land cover changes, directly and indirectly affecting local communities and the natural landscape via complex, interrelated and often long-lasting impacts. With the impending increase in demand for mineral resources, the need for robust analyses and clear reporting of data on the local and regional changes is considered essential for mining companies to effectively detect, track, sustainably manage and mitigate impacts. Remote sensing and GIS methods hold the potential to assist and improve conventional social science approaches; they provide the means to spatially capture and triangulate data from the dynamic mining landscape to study past and ongoing socio-environmental impacts. This thesis aims to investigate the use of spatially explicit GIS and Remote Sensing methods for assessing the social and environmental impacts of mining. To achieve this, the chapters (1) extensively reviewed prior studies that integrated GIS and remote sensing with social science methodologies to evaluate socio-economic and environmental mining impacts, (2) compile recommendations on how the integration of GIS, Remote Sensing, and Social Science can be enhanced for future research on the socio-economic and environmental implications of mining, and (3) characterise the land cover changes in a mining landscape in Didipio, Philippines, and its concurrent impacts on socio-environmental land uses.